1997
DOI: 10.1523/jneurosci.17-11-04223.1997
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinases-1 (TIMP-1) Is Differentially Induced in Neurons and Astrocytes after Seizures: Evidence for Developmental, Immediate Early Gene, and Lesion Response

Abstract: We investigated in vivo the expression of the tissue inhibitor of metalloproteinases-1 (TIMP-1) in the rat CNS after kainate (KA)-induced excitotoxic seizures. In situ hybridization revealed that TIMP-1 mRNA is induced rapidly and massively in most regions of the adult forebrain after KA treatment. Neuronal activity seems to be necessary but not sufficient to trigger TIMP-1 induction, because it is not observed in seizing 10-d-old pups, unlike what is observed in 21-and 35-d-old animals after seizures. The rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
116
3
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 71 publications
16
116
3
2
Order By: Relevance
“…Whereas the dendritic translocation of MMP-9 mRNA appears to be an especially plausible and attractive explanation for our result, one should also alternatively consider enhanced mRNA accumulation in local glia. However, we did not observe either punctate distribution of the MMP-9 within other parts of hippocampus or its upregulation in lesioned pyriform cortex, patterns that are typical for glia gene expression in neurodegeneration (Rivera et al, 1997).…”
Section: Regulation and Mechanisms Of Mmp-9 Expression In Adult Rat Bcontrasting
confidence: 88%
See 1 more Smart Citation
“…Whereas the dendritic translocation of MMP-9 mRNA appears to be an especially plausible and attractive explanation for our result, one should also alternatively consider enhanced mRNA accumulation in local glia. However, we did not observe either punctate distribution of the MMP-9 within other parts of hippocampus or its upregulation in lesioned pyriform cortex, patterns that are typical for glia gene expression in neurodegeneration (Rivera et al, 1997).…”
Section: Regulation and Mechanisms Of Mmp-9 Expression In Adult Rat Bcontrasting
confidence: 88%
“…Recently, it has been demonstrated that neuronal TIMP-1 is regulated by synaptic activity (Nedivi et al, 1993;Rivera et al, 1997;Jaworski et al, 1999). This prompted us to address the hypothesis that MMPs are involved in the activity-dependent reorganization of neuronal architecture.…”
mentioning
confidence: 99%
“…Levels of TIMP-1 expression were found to be increased in the hippocampal formation after transient forebrain ischemia or seizure and in the retinal ganglion cell layer after elevation of intraocular pressure (Rivera et al, 1997(Rivera et al, , 2002Jourquin et al, 2005). Manipulations increasing TIMP-1 were shown to protect neurons in dissociated and organotypic hippocampal cultures from excitotoxicity but not from apoptosis induced by withdrawal of nerve growth factor or chemical-induced ischemia (Tan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chez le rat, l'expression de TIMP-1 est fortement augmentée dans les neurones des grains de l'hippocampe quelques minutes après la reperfusion isché-mique ou le déclenchement de crises convulsives. Quelques jours plus tard, la synthèse de TIMP-1 est induite dans des astrocytes réactifs proches des neurones lésés, mais pas dans la microglie réactive [8,9]. Il a également été décrit une augmentation des concentrations de MMP-9 et -2 après une crise d'épi-lepsie ou une ischémie cérébrale chez le rat [9- adapté les techniques de zymographie in situ pour étudier dans le système nerveux, et avec une résolution cellulaire, les modulations de l'activité des MMP au cours de diffé-rents processus pathologiques.…”
Section: Excitotoxicité Et Mort Neuronaleunclassified